Ag nanosheets grown on Cu nanowire-based flexible films for sensitive non-enzymatic glucose sensors. (23rd December 2019) - Wei, Chenhuinan; Kang, ChenXia; Liu, Qiming
Abstract: Cu nanowire (Cu NW) and Ag nanosheet (Ag NS) bimetallic nanocomposites were fabricated on a flexible polyethylene terephthalate (PET) slice for non-enzymatic glucose sensing via a facile two-step approach, vacuum filtration, and galvanic displacement. Low-cost Cu NW-based conductive films were employed as the conductive substrates to substitute the traditional glassy carbon electrodes or indium tin oxide electrodes. The highly stable Ag NSs grow directly on the surface of Cu NWs without additional binders. The AgNO3 concentration and displacement time were adjusted to control the consumption of Cu NWs and the growth of Ag nanostructures. With the large load of Ag and the great connection of Cu NWs, a high sensitivity of 2033 μ A mM −1 cm −2, a fast amperometric response of 2 s, a wide linear range of 0.0015–4.02 mM, and a satisfactory result in human serum analysis were obtained by this novel Ag NS/Cu NW/PET sensor. Especially the sensitivity of the sensor was over four-fold higher than that of pure Cu NWs/PET, benefiting from the synergistic effect of bimetals. Furthermore, the Ag NS/Cu NW/PET sensor demonstrated a stable amperometric signal against mechanical bending. The material holds promise to use to fabricate flexible electrochemical devices.